EVALUATION OF THE EDUCATION SCIENCE MASTERY IMPACT IN ENVIROMENTAL FORMATION IN SECONDARY SCHOL TEACHER´S IN MATANZAS PROVINCE. - Mesa Herrera, Gudelia A.; Rodríguez Reyes, Oxana; Pérez Benítez, Inés María (Atenas, 2013)
The work deals with the evaluation of the positive impact in the Education Science Mastery in the environmental formation in Secondary School teacher´s in Matanzas province. Starting from analysis of documents, observation of thesis defense and tutors reviews to determine the achievements and shortcoming still present in their preparation to take measures in order to improve the work about environmental education to the students this level of teaching.